Effect of dietary protein content during recovery from high-intensity cycling on subsequent performance and markers of stress, inflammation, and muscle damage in well-trained men - Rowlands, D. S.; Rössler, K.; Thorp, R. M.; Graham, D. F.; Timmons, B. W.; Stannard, S. R.; Tarnopolsky, M. A. (Applied Physiology, Nutrition, and Metabolism, 2007)
Nutrition is an important aspect of recuperation for athletes during multi-day competition or hard training. Post-exercise carbohydrate is likely to improve recovery, but the effect of protein is equivocal. The objective of this study was to determine the effect of post-exercise dietary protein content imposed over a high-carbohydrate background on subsequent performance. Using a crossover design, 12 cyclists completed 3 high-intensity rides over 4 days. Day 1 comprised 2.5 h intervals, followed by repeat-sprint performance tests on days 2 (15 h post) and 4 (60 h post), interspersed with a rest day. During 4 h recovery on days 1 and 2, cyclists ingested either 1.4 g·kg-1·h-1 carbohydrate, 0.7 g/kgh protein and 0.26 g/kg·h fat (protein-enriched) or 2.1 g/kg.h carbohydrate, 0.1 g/kg·h protein, and equal fat (control). At other times, cyclists ingested a standardized high-carbohydrate diet. Anabolism was gauged indirectly by nitrogen balance, stress and inflammation via cortisol and cytokines, skeletal-muscle membrane disruption by creatine kinase, and oxidative stress by malonyl dealdehyde. Sprint mean power was not clearly different on day 2 (0.0%; 95%CL: ±3.9%), but on day 4 it was 4.1% higher (±4.1%) in the protein-enriched condition relative to control. Reduced creatine kinase was possible (26%; ±30%) but effects on oxidative stress, inflammatory markers, and cortisol were inconclusive or trivial. Overnight nitrogen balance was positive in the protein-enriched condition on day 1 (249 ± 70 mg N·kg FFM-1; mean ± SD), but negative (-48 ± 26 mg N·kg FFM-1) in the control condition. A nutritive effect of post-exercise protein content was not discernible short term (15 h), but a delayed performance benefit (60 h) was observed following protein-enriched high-carbohydrate ingestion.